Predation of diamondback moth larvae and pupae by Euborellia annulipes - Nunes, Gilmar da Silva [UNESP]; Vitoriano Dantas, Thais Aparecida; Souza Figueiredo, Wennia Rafaely; Souza, Mileny dos Santos de; Nascimento, Izabela Nunes do; Batista, Jacinto de Luna (Univ Federal Rural Pernambuco, 2018)
Diamondback moth, Plutella xylostella, is considered the most important pest species of brassica crops and Euborellia annulipes can exhibit potential for its control. This work recorded the consumption of 4th-instar larvae and pupae of P. xylostella by nymphs and adult females of the ring-legged earwig E. annulipes at different ages: 2, 4, 6, 8 and 10 days old. Nymphs in the 3rd-instar and females of E. annulipes consumed daily more P. xylostella larvae than pupae. The consumption of diamondback moth pupae became constant as the 5th-instar nymphs of the predator develop. In the other hand, the consumption of larvae decreases when nymphs are closer to molt. Female, regardless of its age, consumed more larvae than pupae of P. xylostella.
Keywords: brassica; earwigs; integrated management; Plutella xylostella